An Experimental Study on Stress Concentration Around a Hole Under Combined Bending and Stretching Stress Field. (2016) - Ghuku, Sushanta; Saha, Kashi Nath
Abstract: It is well known that in a loaded structural member, redistribution of stresses occur near a discontinuity, thus increasing the induced stress value significantly over the nominal stress value. The paper presents an experimental study on existence of stress concentration in the vicinity of drill hole present in master leaf of a leaf spring bundle. For the purpose of experimentation a leaf spring testing rig is set up and master leaf of an automobile leaf spring is procured. To investigate the state of stress field produced in the master leaf spring, load-deflection behavior of the master leaf is first studied experimentally. Experimental stress concentration factors are obtained by mounting strain gauges at different locations, around the central drill hole of the master leaf. In corresponding theoretical analysis, the master leaf spring is modeled as a curved beam with a circular hole on its centre line subjected to combined bending and stretching. Theoretical and experimental stress concentration factors are reported in an appropriate form which will facilitate to undertake rigorous theoretical analysis of stress distribution around geometric discontinuities in beam under different loading conditions.